PENGARUH BOARD CHARACTERISTIC TERHADAP FIRM PERFORMANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Acchedya Anugrahani; Deddy Marciano; Bertha Silvia Sutejo (CALYPTRA, 2018)
This study aims to investigate the determinants of board characteristics such of of dari proportion woman director, education level, average board tenure, director size, independent director, firm age dan firm size of companies’ listed in the Indonesian Stock Exchange using agency theory. This Study uses the quantitative approach and multiple linear reggresion to analyze the data. The target populations of this study are manufacturing companies registered in Indonesia Stock Exchange in 2012-2016 which are equal to 535 year observations.